2021
DOI: 10.3390/v13122437
|View full text |Cite
|
Sign up to set email alerts
|

Atovaquone and Berberine Chloride Reduce SARS-CoV-2 Replication In Vitro

Abstract: Epidemic RNA viruses seem to arise year after year leading to countless infections and devastating disease. SARS-CoV-2 is the most recent of these viruses, but there will undoubtedly be more to come. While effective SARS-CoV-2 vaccines are being deployed, one approach that is still missing is effective antivirals that can be used at the onset of infections and therefore prevent pandemics. Here, we screened FDA-approved compounds against SARS-CoV-2. We found that atovaquone, a pyrimidine biosynthesis inhibitor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…As well as the development of inhibitors to slow viral replication, such as 3C-like proteases, papain-like protease, and angiotensin-converting enzyme II, immunosuppressive treatments may be useful in preventing the cytokine storm in the later stages of COVID-19, a major cause of patient death. 1 , 2 , 3 , 4 In this study, we focused on identifying potential prophylaxes for SARS-CoV-2 infection, specifically an immune-enhancing compound derived from natural products. Immune-enhancing compounds are generally classified as those capable of enhancing the non-specific immune system response by promoting the activity of phagocytes such as neutrophils and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…As well as the development of inhibitors to slow viral replication, such as 3C-like proteases, papain-like protease, and angiotensin-converting enzyme II, immunosuppressive treatments may be useful in preventing the cytokine storm in the later stages of COVID-19, a major cause of patient death. 1 , 2 , 3 , 4 In this study, we focused on identifying potential prophylaxes for SARS-CoV-2 infection, specifically an immune-enhancing compound derived from natural products. Immune-enhancing compounds are generally classified as those capable of enhancing the non-specific immune system response by promoting the activity of phagocytes such as neutrophils and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that berberine has many pharmacological activities, including antihyperlipidemic, antidiabetic, antiobesity, anticancer, anti-inflammatory, antioxidant, neuroprotective, cardioprotective, immunomodulatory, and other effects [ 52 , 53 , 54 , 55 ]. Recently, many studies have been conducted to examine the role of berberine in COVID-19 [ 56 , 57 , 58 , 59 ] ( Figure 1 ).…”
Section: Berberinementioning
confidence: 99%
“…Moreover, subsequent in vitro tests have showed a strong inhibition of the replication of different SARS-CoV-2 variants (alpha, beta and delta) in Vero E6 and Calu-3 cells [ 149 ]. Additionally, atovaquone was able to significantly reduced virus replication and infection in human lung cells, Vero cells and human hepatocytes [ 150 , 151 ]. However, concerning atovaquone’s ability to reduce virus production in airway epithelium cultures, inconsistent results have been obtained [ 149 , 150 ].…”
Section: Antimalarial Drugsmentioning
confidence: 99%
“…Additionally, atovaquone was able to significantly reduced virus replication and infection in human lung cells, Vero cells and human hepatocytes [ 150 , 151 ]. However, concerning atovaquone’s ability to reduce virus production in airway epithelium cultures, inconsistent results have been obtained [ 149 , 150 ].…”
Section: Antimalarial Drugsmentioning
confidence: 99%